Direito à educação: o pão nosso de cada dia - Seixas, Taysa Matos (2014)
This dissertation deals with the themes of the Right to Education, based on philosophical, ethical, legal and human rights principles, investigating the need for secure that right for the formation of the citizen as a subject of law. In each moment of the research focus efforts aimed at realizing the existing relationship between the Right to Education the construction of citizenship and therefore a fairer and less exclusionary society. Even aware of the complexity of the issue, challenge ourselves to clarify a number of aspects pertaining to "answer" the central question of this research exposed in the introduction. We believe that the result of this work, even with its limitations, can contribute to strengthening the building of a culture to the experience of the Right to Education as a fundamental to the effectiveness of Human Rights, as well as for the liberation and emancipation of human beings in society, as in the proposed Paulo Freire. This problem-based education and emancipatory proposal, which excels in the teaching-learning process and is constructed from the reality of the subject leads us to reflect on the need to overcome situations of human rights violations that limit full citizenship and exclude the subject from the social scene. The Right to Education, so their legal, ethical, political and social, enables engagement with the practice of human rights is an important tool for organizing and social transformation where everyone is offered the same opportunities and the same rights guaranteed.